(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the research field of Agronomy Division, Bangladesh Agricultural Research Institute, Joydebpur, Gazipur during the rabi season of 2013-2014 to find out the optimum dose of herbicide (Teana 9 EC) to control weeds in brinjal field for getting higher yield. Six treatments, viz.: (i) Teana 9 EC @ 750 ml ha-1 spraying on 15 DAS and 45 DAS, (ii) Teana 9EC @1000 ml ha-1 spraying on 15 DAS and 45 DAS, (iii) Teana 9EC @ 1250 ml ha-1 spraying on 15 DAS and 45 DAS, (iv) Teana 9EC @ 1500 ml ha-1 spraying on 15 DAS and 45 DAS, (v) two hand weddings, and (vi) no weeding (control) were used in the experiment. Among the weed species, Bathua (Chenopdium album), Durba (Cynodon dactylon), Anguli (Digitaria sanguinalis), Helencha (Jussiaea repens), Hatishur (Heliotropium indicum), Shama (Echinochola crusgalli), Swetlomy (Gnaphalium japonicum), Mutha (Cyperus rotundus), Shaknote (Amaranthus viridis), Gaicha (Paspalum commersonii), Chapra (Eleusine indica), Bon Masur (Vicia sativa) were found dominant in wheat field. The result showed that the highest dry weight of weeds at 30 and 60 DAS were 12.24 and 24.12 gm-2 in control plot, whereas the lowest weed dry weight was observed in two hand weedings. The maximum weed control efficiency over control both at 30 and 60 DAS were 79.41 and 74.32%, respectively in the treatment with two hand weedings. The highest number of fruits plant-1, single fruit weight (g), fruit length (cm) and yield (t ha-1) was found in the treatment having two hand weedings and the lowest in no weeding (control). Though the weed control efficiency (WCE) was the highest in the treatment with two hand weedings due to higher labor cost but the maximum benefit cost ratio was the highest when Teana 9EC @ 1500 ml/ha was sprayed two times on 15 and 45 DAS. Bangladesh Agron. J. 2015, 18(1): 113-119